2016
DOI: 10.1038/srep33711
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and cancer risk: A meta-analysis of prospective observational studies

Abstract: Meta-analyses on coffee and cancer incidence mainly restricted to limited cancers. We carried out a more comprehensive meta-analysis of cohort studies to explore association between coffee and most cancer types. We conducted comprehensive search and summarized relative risk (RR) and 95% confidence intervals for the highest versus lowest coffee intake and cancer using STATA12. We conducted dose-analysis if result suggested significant association. The publication bias was evaluated with begg’s and egger’s test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 141 publications
(165 reference statements)
2
73
2
2
Order By: Relevance
“…The cohort studies from the excluded meta‐analyses for coffee intake were all included in the newer meta‐analyses . The other excluded meta‐analyses also had fewer cohorts included, despite being published more recently . Upon further comparison between the two and further investigation of the original studies, the excluded meta‐analysis also reported some incorrect relative risks in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The cohort studies from the excluded meta‐analyses for coffee intake were all included in the newer meta‐analyses . The other excluded meta‐analyses also had fewer cohorts included, despite being published more recently . Upon further comparison between the two and further investigation of the original studies, the excluded meta‐analysis also reported some incorrect relative risks in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…We found HPV to be more common among coffee drinkers (11.54%, 10/102 samples) than non‐coffee drinkers (3.05%, 12/492 samples) ( P = 0.002). On the other hand, coffee consumption appears to have a protective benefit in oral cancer …”
Section: Discussionmentioning
confidence: 99%
“…The indole group of Trp-2239 interacted with the morpholine ring and stacked with the pyrido-pyrimidine group in a way similar to ATP and Torin2. Trp-2239 contact is responsible for higher specificity over PI3K isoforms [2,18,24,35,36] One morpholine ring is surrounded by hydrophobic and the other by hydrophilic residues [37]. The side chain of Met-2345part of the N-lobe opposite to adenine binding pocket and Ile-2356 part of hydrophobic adenine site were involved in hydrophobic interactions with pyrido-pyrimidine group.…”
Section: Docking Analysis Of Azd 2014mentioning
confidence: 99%
“…Member of Phosphoinositide 3-kinase (PI3K) family, mechanistic/mammalian target of rapamycin (mTOR) is a serine/threonine kinase and ortholog of yeast TOR protein [1,2]. mTOR is a key regulatory enzyme of PI3K/AKT/mTOR pathway and central modulator of cell growth, metabolism and survival [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation